2013
DOI: 10.1186/1476-9255-10-17
|View full text |Cite
|
Sign up to set email alerts
|

MALP-2 pre-treatment modulates systemic inflammation in hemorrhagic shock

Abstract: BackgroundTLR-2 is expressed on the surface of leucocytes, lung and liver tissue and initiates the activation of immune response after interaction with components of the bacterial cell wall. In this experiment we investigated whether immunostimulation with TLR-2 agonists under conditions of sterile inflammation (hemorrhagic shock (HS)) may affect the immune response and remote organ inflammation.MethodsMale C57/BL6 mice were subjected to standardized pressure-controlled HS (MAP of 35 mmHg for 90 minutes). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Thus, observations reported by Pfeifer et al . were confirmed [ 9 ]. Also, Feterowski et al described no elevation of IL-10 after systemic injection of MALP-2 in mice.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Thus, observations reported by Pfeifer et al . were confirmed [ 9 ]. Also, Feterowski et al described no elevation of IL-10 after systemic injection of MALP-2 in mice.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, our findings are in line with data published by Zeckey et al who also did not observe a significant impact of MALP-2 on pro-inflammatory mediator levels (IL-6, TNF-α, and MIP-1α) 96 h after induction of isolated sepsis [ 10 ]. In a murine model of isolated TH, Pfeifer et al found that MALP-2 application before the insult resulted in a more balanced migration of PMN into different body compartments instead of accumulating in one [ 9 ]. Based on this finding, it might be speculated that a similar phenomenon is also applicable for immunocompetent cells after the MALP-2 application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Injuries to large vessels cause hypovolemia and generalized ischemia. This leads to microcirculatory disturbances, metabolic changes, and depression of the immune system (1)(2)(3)(4)(5). In addition, it is associated with low organ perfusion and an imbalance between O 2 demand and O 2 supply (6).…”
mentioning
confidence: 99%